LEGAL ASPECTS OF INCAPACITATED CHILDREN HEALTHCARE - S.Ya. Volgina; Z.M. Aminova; S.Sh. Yafarova ("Paediatrician" Publishers LLC, 2008)
The article provides analyses of key legal and regulatory acts that regulate medical and social care provided to incapacitated children and there families. The article specifies main measures for healthcare and social support provided to children of this category, mentions current achievements and remaining obstacles for providing complex rehabilitation of invalid children.Key words: invalid children, rehabilitation, healthcare.